1992
DOI: 10.1093/clind/15.6.910
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Candidiasis in Addicts Who Use Brown Heroin: Report of 83 Cases and Review

Abstract: From November 1983 to April 1990, disseminated candidiasis was diagnosed in 83 heroin addicts at our institution. All patients had consumed brown heroin diluted in fresh lemon juice. Sixty-two (75%) had skin lesions, 41 (49%) had ocular lesions, and 35 (42%) had one or several costochondral tumors. Candida albicans was grown in culture or histopathologically identified in 34 cases (41%). The patients who had only cutaneous lesions were treated with ketoconazole, and they were all cured. The patients with ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 99 publications
2
65
0
3
Order By: Relevance
“…Jeśli osoba uzależniona stosuje brązową heroinę rozpuszczaną w soku cytrynowym trzeba dołączyć lek przeciwgrzybiczy, przypuszczając, że czynnikiem etiologicznym mogą być Candida spp. (nie Candida albicans) [435]. Po wyizolowaniu mikroorganizmu odpowiedzialnego za zakażenie należy włączyć leczenie celowane.…”
Section: Leczenie Przeciwdrobnoustrojoweunclassified
“…Jeśli osoba uzależniona stosuje brązową heroinę rozpuszczaną w soku cytrynowym trzeba dołączyć lek przeciwgrzybiczy, przypuszczając, że czynnikiem etiologicznym mogą być Candida spp. (nie Candida albicans) [435]. Po wyizolowaniu mikroorganizmu odpowiedzialnego za zakażenie należy włączyć leczenie celowane.…”
Section: Leczenie Przeciwdrobnoustrojoweunclassified
“…AAB were also implied or suspected to be responsible for other types of infections, including, in particular, bacteremia in patients for whom the probable source of infection was an indwelling device (1,12,17,27). The known use of acidic substances such as vinegar or lemon juice to dilute heroin (2,28) and the potential contamination of batches of compounds for intravenous drug abuse by AAB (32,33) make us speculate that patient 1 was contaminated after intravenous drug injection, probably during his hospitalization, as he was apyretic at the time of admission. An improvement of the clinical condition of this immunocompetent patient was observed with ceftriaxone treatment, even though this molecule was not active in vitro, without removing the central venous catheter placed for antifungal drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrated that lemon juice can support C. albicans growth at room temperature [19] and was associated with disseminated candidiasis or Candida endophthalmitis in IVDUs, since lemon juice was used for preparation of brown heroin for intravenous use [4,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors include the presence of prosthetic valves, short term indwelling catheters, broad spectrum antibiotic use, history of health associated care and intravenous drug use [1,2]. A distinct clinical syndrome of disseminated candidiasis in heroin abusers exists [3] and it is associated with the use of lemon in the preparation of heroin prior to injection [4]. Manifestations include development of lesions in the skin of hair bearing areas such as the scalp, the beard, and the axillary and pubic areas where pustules are formed in the location of follicles, ocular lesions such as episcleritis and chorioretinitis, and lesions in bone and costal cartilage [3].…”
Section: Introductionmentioning
confidence: 99%